2016
DOI: 10.9790/1959-0504012832
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Risk Factorsrelated to Hypothyroidism for Adult Patient at Bagdad Teaching Hospitals

Abstract: Abstract:The objective are To assess of contributing factors related tohypothyroidismfor adultpatients,and find out the relationship between some demographic characteristic (age, gender, level

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…These results are sustained by study was conducted in Saudi Arabia (9) It approved that females are constituted (72.2%). The current study is consistent with another study was done in Saudi Arabia (10) stated that highest percentages (32%) of patients with hypothyroidism and mean age 44.1 ± 16.3 in the age group (40-49) years (fifth decade).As well as, these findings are supported by Iraqi study (11) reported that (30%) of study participants were primary school graduated with hypothyroidism.…”
Section: Discussionsupporting
confidence: 92%
“…These results are sustained by study was conducted in Saudi Arabia (9) It approved that females are constituted (72.2%). The current study is consistent with another study was done in Saudi Arabia (10) stated that highest percentages (32%) of patients with hypothyroidism and mean age 44.1 ± 16.3 in the age group (40-49) years (fifth decade).As well as, these findings are supported by Iraqi study (11) reported that (30%) of study participants were primary school graduated with hypothyroidism.…”
Section: Discussionsupporting
confidence: 92%